A Perspective on Late-Stage Aromatic C–H Bond Functionalization - Zhang, Li; Ritter, Tobias (Journal of the American Chemical Society, 2022)
Late-stage functionalization of C–H bonds (C–H LSF) can provide a straightforward approach to the efficient synthesis of functionalized complex molecules. However, C–H LSF is challenging because the C–H bond must be functionalized in the presence of various other functional groups. In this Perspective, we evaluate aromatic C–H LSF on the basis of four criteriareactivity, chemoselectivity, site-selectivity, and substrate scopeand provide our own views on current challenges as well as promising strategies and areas of growth going forward.